Bad habits ; IVth degree burns ; Prison without bars [videorecording] - Lazaro, Cheche (The Probe Team, 1994)
Documents the violence created by the Abu Sayaff group in Basilan; the U.P. College of Medicine graduating class with their "sunugan"; and the Iwahig Penal Colony in Palawan.